2001
DOI: 10.2139/ssrn.269668
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of E-Commerce Announcements on the Market Value of Firms

Abstract: How do the returns to e-commerce initiatives involving digital goods compare to initiatives involving tangible goods? We examine these issues using event study methodology and assess the cumulative abnormal returns to shareholders (CARs) for 251 e-commerce initiatives announced by firms between October and December 1998. The results suggest that e-commerce initiatives do indeed lead to significant positive CARs for firms' shareholders. While the CARs for conventional firms are not significantly different from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
150
2
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(157 citation statements)
references
References 49 publications
2
150
2
3
Order By: Relevance
“…Related work found that e-commerce announcements (Subramani and Walden 2001) and Internet channel addition (Geyskens et al 2002) were correlated with changes in market value.…”
Section: ---2mentioning
confidence: 99%
“…Related work found that e-commerce announcements (Subramani and Walden 2001) and Internet channel addition (Geyskens et al 2002) were correlated with changes in market value.…”
Section: ---2mentioning
confidence: 99%
“…Positive signifi cant reaction was found only for non-innovative ICT investments. E-commerce applications have been analysed also by [23], [31].They found positive signifi cant impact of e-commerce use on the market value of companies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There were many studies investigating effect of special types of investments, as for instance, in e-commerce [15], [31], in ERP [19], or in CRM, etc., however they were conducted only on the markets of developed economies.…”
Section: Ict Investment Typementioning
confidence: 99%
“…기존 전략적 동맹이나 인수합병 관 련 연구는 i) 두 지배구조가 상이함에도 불구 하고 이를 호환적(interchangeable)으로 일반 화하여 사용하는 연구 [16,25], ii) 둘 가운데 하나의 지배구조에만 초점을 둔 연구 [20,22] 률은 다음과 같이 계산하였다 [21,37]. [4,37]. …”
Section: 서 론unclassified